Evaluasi Fungsi Ekologis dan Keindahan Taman Bunga (Lapangan Merdeka) Pematang Siantar - A I Ramadhani; E Fahriza; Hendra A (Jurnal MESIL (Mesin Elektro Sipil), 2023)
The increase in population has resulted in an increase in the amount of development in Pematangsiantar City which has a negative impact on the decline in environmental quality. City parks are an important aspect in minimizing this impact. City parks have ecological functions that function as microclimate controllers, noise absorbers, windbreakers, besides that city parks also function as beauty in the city. The purpose of this research is to evaluate the extent to which the park functions in improving urban quality. The ecological function analyzed is the function of vegetation as a temperature control, humidity control, windbreaker, noise reducer. Analysis of the aesthetic function was also carried out in this study to determine the extent to which the park provides beauty to the city. Analysis of ecological function and aesthetic uses the KPI method to determine the score of vegetation in ecological function and aesthetic. The THI method is used to determine the condition of the microclimate. Measurement of noise levels to determine the function of the park in reducing noise. The distribution of questionnaires was carried out to obtain responses from park users regarding the ecological function and aesthetic of the park to compare with the results of previous methods. Taman Bunga has 28 species with a total of 372 individuals. The results of the KPI assessment show that the Taman Bunga has the best function in beauty. Vegetation in the Flower Garden has an effect in controlling temperature and humidity can be seen from the results of temperature measurements inside and outside the park has a difference of 1.5 ° C, and a humidity difference of 2.55%. Although it has a THI value that does not meet ideal comfort.